(3QSGdI aj JhLjg fUH (B"(3aVdkG(B"s - (3LeGd GdOjf CHh YHO Gddg,J (B761 (3g` s
(3ChdgG (B:s
(3bGd SCdfj HYV GdENhGf, hCfG Ydi LfGM SaQ, Yf JhLjg GdfUH aj fMh bhd GdbGFd(B: s
(3BNQgG (B:s
(3hdh hbaJ dge Ydi Pdc dhLOJ aj cdGege eKd Pdc Ch CeKGdg fLR hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B126 - (3U(B134s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B23 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B16 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B135 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(25 (3O(B) s
Keywords: (3GdfMhs